Respostas
respondido por:
1
y=x² * cos x + 4x * senx
y'=[(x²)' * cos x +(x²) * (cos x)' ] + [(4x)' * senx +(4x) * (sen x)']
y'=[2x* cos x +(x²) * (-senx)] + [(4)* senx +(4x) * (cos x)]
y'=2xcos x -x²senx +4senx+4xcos x
y'=4x *cos x -(x²-4)*sen x
y'=[(x²)' * cos x +(x²) * (cos x)' ] + [(4x)' * senx +(4x) * (sen x)']
y'=[2x* cos x +(x²) * (-senx)] + [(4)* senx +(4x) * (cos x)]
y'=2xcos x -x²senx +4senx+4xcos x
y'=4x *cos x -(x²-4)*sen x
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás